(untitled) (Jurnal SPEKTRUM, 2026)
Line coding is a process of converting digital data into electrical signals so that they can be transmitted in a fiber optic network. Commonly used line coding is NRZ and RZ. Line coding characteristics are determined by the selection of Rectangular shape, Amplitude, Bias, Position, Rise Time and Fall time. The rise time of a signal is defined as the time required for the signal to change from 10% to 90% of the maximum value. In this study, the effect of increasing the rise time value on RZ and NRZ line coding was observed compared to Q Factor and BER. The rise time value starts from 0.05 bits with an increase of 0.05 until it reaches a value of 1 bit. The results obtained show a change in the signal shape from the edial form at a rise time of 0.05 bits to a non-edial form at a value of 1 bit. RZ line coding shows no significant change in Q Factor and BER from changes in rise time values, but NRZ line coding shows a decrease in Q Factor by 10.57% and BER by 80.9%.